Photocatalytic and Photoelectrocatalytic Degradation of Methyl Orange Using Graphite/PbTiO3 Composite - Candra Purnawan; Sayekti Wahyuningsih; Pramudita Putri Kusuma (Indonesian Journal of Chemistry, 2016)
Synthesis of graphite/PbTiO3 composite as a catalyst in photodegradation and photoelectrodegradation process of methyl orange have been conducted. The purposes of this research are to study the effect of radiation time, composition of composite, voltage and pH of solution for methyl orange degradation. Photodegradation process of methyl orange was carried out for 5; 10; 15; 20; 25 and 30 min. Ratio of graphite : PbTiO3 (w/w) were varied at 1:3; 1:2; 1:1; 2:1 and 3:1. Meanwhile, the applied voltages were 7.5; 10 and 12.5 V and the photoelectrodegradation was conducted under pH condition of 3; 7; and 11, respectively. The result showed that optimum composition of graphite/PbTiO3 in the methyl orange photodegradation was obtained at 1:1 ratio for 30 min with degradation up to 90.43% ± 0.062. The degradation reaction follows first order reaction with a rate constant of 0.0688 min-1. The optimum voltage is 10 V, in which it reduced the methyl orange concentration up to 92.65% ± 0 with a rate constant 0.0941 min-1 for first order reaction. The optimum pH is pH = 11, that provide methyl orange reduction up to 95.28% ± 0.082.